Role of small non-absorbing macromolecules in red blood cell adhesion. - Tan, Kwan Ling. (2013)
Red blood cells (RBC) aggregation is a phenomenon whereby the red blood cells form aggregates when suspended in plasma or solutions containing large polymer. This aggregation process is reversible, whereby the aggregates can be dispersed by mechanical or fluid forces, however it may reform once the forces are removed. RBC aggregation may cause disruption to the blood flow which may result in serious consequence. It is therefore in the aim to have more understanding to the mechanism of RBC aggregation in order to prevent occurrence of such aggregation to ensure smooth blood flow. Understanding RBC aggregation would also help in understanding some diseases related to it.